+0  
 
0
267
2
avatar

trying to find t where 6=sinh^2/3(4t), i'm struggling to understand the inverse of sinh when the power isn't one

Guest Apr 5, 2017
 #1
avatar
0

Solve for t:
6 = 4 t (sinh(x))^(1/3)^2

4 t (sinh(x))^(1/3)^2 = 4 t sinh^(2/3)(x):
6 = 4 t sinh^(2/3)(x)

6 = 4 t sinh^(2/3)(x) is equivalent to 4 t sinh^(2/3)(x) = 6:
4 t sinh^(2/3)(x) = 6

Divide both sides by 4 sinh^(2/3)(x):
Answer: | t = 3/(2 sinh^(2/3)(x))

Guest Apr 5, 2017
 #2
avatar+7164 
0

Can you first raise both sides to the 3/2 power...then take the sinh inverse of both sides?

 

Like this:

 

\(6=\sinh^{\frac23}(4t) \\~\\ \\~\\ 6^{\frac32}=\sinh^{\frac23*\frac32}(4t) \\~\\ 6\sqrt{6}=\sinh(4t) \\~\\ \sinh^{-1}(6\sqrt{6})=4t \\~\\ \frac{\sinh^{-1}(6\sqrt{6})}{4}=t \\~\\ t \approx 0.845 \text{ radians} \\ t \approx 48.443 \text{ degrees}\)

 

Assuming that was the question.

It took me awhile to check this because in most calculators you need to input it like this:

[sinh(4(0.845))]^(2/3)  smiley

 

*edited to clarify that it is 0.845 radians, and to add degrees.*

hectictar  Apr 5, 2017
edited by hectictar  Apr 5, 2017

4 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.